Approaching Islamic architectural heritage studies through problem based learning - Abdullah, Fadzidah (EDULEARN, 2009)
This paper deals with an innovation of approaching Islamic Architectural Heritage through an educational learning approach named Problem Based Learning (PBL). The Department of Architecture (DoA), in Kulliyyah of Architecture and Environmental Design (KAED), of International Islamic University Malaysia (IIUM), has implemented the so-called Problem Based Learning in one of its core courses, named AAR 3201: Heritage Studies. Although PBL has not been thoroughly discussed in numerous forums, seminar, and conferences of architectural education through out the world, yet this approach has always been unconsciously implemented in learning and teaching of architecture. Similarly in DoA, this theoretical educational approach was not discussed when the process of developing the course was carried out, yet recent analysis on the course shows the existence of PBL essence in learning and teaching process of the course. The implementation of PBL educational approach has proven to effectively develop students’ independency in learning, and enhance their proficiency in understanding Islamic Architectural Heritage. Students are also found to appreciate Islamic Architectural Heritage better through this PBL educational approach as compared to learning the subject in traditional way of listening to lectures. This course of Islamic Architectural Heritage requires students to initially choose old buildings with heritage quality to be measured and researched for the purpose of producing comprehensive documentation of the buildings and their history, in the format of report, construction drawings, presentation drawings, architectural model, miniature artefact, digital multimedia documents etc. After buildings are identified, students are expected to have field work of measuring the buildings, and researching for historical and constructional background of the buildings. Based on students and lecturers feedback, the experiential and practical qualities of PBL approach implemented in this Heritage Studies course have effectively thought students to gather knowledge of Islamic Architectural Heritage better than theoretically teaching them via lectures in history of architecture classes. Indeed, more and more theoretical courses in architectural education should be implemented using Problem Based Learning educational approach to enhance students’ competencies in becoming talented architects.